2021
DOI: 10.1200/jco.2021.39.15_suppl.10559
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors associated with uptake of lung cancer screening among individuals at higher risk.

Abstract: 10559 Background: Lung cancer is the leading cause of cancer death in the U.S, accounting for about 25% of all cancer mortality. The U.S Preventive Services Task Force has recommended annual screening for lung cancer using low-dose computed tomography (LDCT) scanning for individuals at higher risk (aged 55-80 years with a >30 pack-year smoking history). Early detection using LDCT scanning reduces lung cancer specific mortality by 20%. Despite its efficacy, the uptake of annual lung cancer screening among h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In general, cancer screening tests are associated with socioeconomic status and smoking behavior, 34 which holds true for LCS. 12 Correlates of LCS also include health care access, 23 COPD, prior cancer, 13 , 22 , 35 state of residence, 36 receipt of prior vaccination, 12 demographic characteristics (eg, marital status and employment), and smoking history in pack-years. 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, cancer screening tests are associated with socioeconomic status and smoking behavior, 34 which holds true for LCS. 12 Correlates of LCS also include health care access, 23 COPD, prior cancer, 13 , 22 , 35 state of residence, 36 receipt of prior vaccination, 12 demographic characteristics (eg, marital status and employment), and smoking history in pack-years. 12 …”
Section: Methodsmentioning
confidence: 99%
“…In general, cancer screening tests are associated with socioeconomic status and smoking behavior, 34 which holds true for LCS. 12 Correlates of LCS also include health care access, 23 COPD, prior cancer, 13,22,35 state of residence, 36 receipt of prior vaccination, 12 demographic characteristics (eg, marital status and employment), and smoking history in pack-years. 12 To account for socioeconomic status and demographics, we extracted data on age (in 5-year age categories), sex (male and female), race and ethnicity (aforementioned categories), marital status (married, divorced, widowed, separated, never married, or unmarried couple), and educational attainment (never attended school or only kindergarten, elementary or middle school, some high school, high school graduate, some college, and college graduate or more).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected clinically relevant covariables a priori based on prior studies of factors related to uptake of or adherence to LCS, including self-reported race and ethnicity to explore potential disparities in declining LCS. 18 , 19 , 20 , 21 , 22 , 23 For each veteran, we extracted data from the VA Corporate Data Warehouse on demographic characteristics and VA priority status (the VA’s system to determine co-payments). We used a veteran’s residential zip code to estimate median income, and we assessed urbanization using the US Census Bureau Rural-Urban Commuting Area codes.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was documentation (by clinical reminder) that a veteran declined LCS. We selected clinically relevant covariables a priori based on prior studies of factors related to uptake of or adherence to LCS, including self-reported race and ethnicity to explore potential disparities in declining LCS . For each veteran, we extracted data from the VA Corporate Data Warehouse on demographic characteristics and VA priority status (the VA’s system to determine co-payments).…”
Section: Methodsmentioning
confidence: 99%